The Alberta Indigenous Mentorship in Health Innovation Network: approach, activities and reflections of an Indigenous mentorship network programme ... - Barnabe, Cheryl; Henderson, Rita; Murry, Adam; Baker, Janelle; Leason, Jennifer; Currie, Cheryl; Fellner, Karlee; Henry, Robert; Voyageur, Cora; Crowshoe, Lynden (SAGE Journals, 2023)
The Alberta Indigenous Mentorship in Health Innovation (AIM-HI) Network was developed by Indigenous faculty members as an intergenerational mentorship programme for First Nations, Métis and Inuit (FNMI) scholars engaged in health research training programmes. Through activities and funding programmes, the AIM-HI Network provided opportunities for these scholars to strengthen their personal and professional resources and gain resilience along paths to academic success. While generating evidence on wise practices for Indigenous mentorship, we also advocated for systemic change to enable Indigenous scholar promotion and success in academia and in health research more broadly. In this article, we describe the philosophical approach to mentorship and the organizational structure to deliver aligning activities and supports to students. We also reflect on the successes and learnings from our leadership of the Network, including the impact of the coronavirus-19 pandemic on FNMI scholars, and the ways in which the ...